Faktor Penentu Turnover Karyawan PT RIANI Pendekatan Kuantitatif Menggunakan PLS SEM - Agus Djoko Santosa; Evi Nilawati; Rudi Dwi Maryanto; Rilla Sovitriana; Yusuf Maura (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
High turnover rate will have a negative impact on the organization, such as creatinginstability and uncertainty about labor conditions and increasing human resource costs, namely inthe form of training costs that have been invested in employees to recruitment and retraining costs.High turnover also makes the organization ineffective because the company loses experiencedemployees and needs to retrain new employees. This study aims to analyze the effect of the variablecommitment, compensation, and organizational job satisfaction on the intention to leave and analyzethe variables that have the greatest influence on the intention to leave. The sample used was 250respondents. Data analysis using PLS SEM. Commitment has a significant effect on JobSatisfaction, because the T statistic value of 7,997 Commitment has a significant effect on TurnoverIntention, indicated by the T statistic of 2,153 Compensation has a significant effect on JobSatisfaction. because the statistical T value of 2,080 Compensation has a significant effect onTurnover Intention, because the statistical T value of 2,204 Job satisfaction has a significantinfluence on turnover intention, because the statistical T value of 8,388 In an effort to reduceturnover the implications that can be done are to increase commitment and compensation given to itsemployees, Raising awareness to employees that employees have a very important role in advancingthe company.